THE CONTENT, ESSENCE AND TYPES OF MARKETING IN RAILWAY SERVICE ENTERPRISES (American Journal of Business Management, Economics and Banking, 2026)
This article examines the content, essence, and main types of marketing in railway service enterprises under the conditions of the modern service economy. The study is based on the idea that marketing in railway transport should be interpreted not only as a tool for promoting services, but also as an integrated management mechanism aimed at creating customer value, improving service quality, and strengthening the competitive position of railway enterprises. The article analyzes the evolution of marketing theory and summarizes the scientific approaches of leading scholars to the definition of marketing in relation to the service sector.